PENGARUH KOMITMEN, KESAMAAN CITRA, KINERJA LAYANAN DAN NILAI PELAYANAN PERSEPSIAN PADA NIAT UNTUK MELANJUTKAN PERAWATAN YANG DIMEDIASI KEPUASAN DAN KEPERCAYAAN - Kristi T. Sahentumbage; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the intention to continue treatment under the influence of commitment, satisfaction, trust, and perceived service value. Satisfaction and trust are influenced by service performance and image similarity. A high level of commitment, satisfaction, trust and perceived service value will affect the customer's intention to continue treatment. Data were obtained through a questionnaire distributed to salon customers in Serui in a clustered manner. The sampling technique used was purposive sampling of 200 respondents. Hypothesis testing uses Structural Equation Modeling (SEM)analysis. The results of the study show that commitment has a positive effect on intention to continue treatment, satisfaction has a positive effect on intention to continue treatment, trust does not affect intention to continue treatment, perceived service value does not affect intention to continue treatment, service performance has a positive effect on satisfaction, image similarity does not affect satisfaction, and the similarity of the image has no effect on trust.